The women in the sand : a story of Death Valley's original people - Jarvis, Steve (Director); Olmos, Edward James; Leftwood Pictures; Leomark Studios ([Wrightwood, California] : Leftwood Pictures, 2017)
Two elderly women from the Timbisha tribe fight against the US government. USA and against their own tribal council for justice as they try to preserve their ancient culture in the hottest place in the world, Death Valley, CA. --
Originally released as a motion picture in 2017.
Narrated by Edward James Olmos.
Cinematographers, Steve Jarvis, Kate Fosselman, Brian O'Connell ; editors, Kate Fosselman, Clayton Jarvis ; music, Matthew Castaldo.
In English; closed captioning available.
Winner, Accolade Global Film Competition, 2017
Winner, Feature Documentary, Impact Docs Awards, 2017
Keywords: Timbisha Shoshone Tribe; Shoshoni Indians -- Government relations; Cultural property -- Protection; Death Valley (Calif. and Nev.); Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video